PENGARUH IMPLEMENTASI PROGRAM BUMDES TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT DI DESA TONSEWER SELATAN KECAMATAN TOMPASO BARAT KABUPATEN MINAHASA - SUOTH, AYU ENJELIA PATRISIA; LENGKONG, FLORENCE DAICY; DENGO, SALMIN (Sam Ratulangi University, 2019)
The Implementation of BUMDES program is the implementation of economic programs or activities that are managed directly by the village government and the community, whose purpose is to manage and develop the village’s potential. Community economic empowerment is an effort to prosper the community through the implementation of economic activities that can increase people’s income. Based on research, BUMDES Tonsewer Selatan, Tompaso Barat subdistrict has programs work already running well, although there are still programs that have not run smoothly and still have constraints, such as in the implementation of hollow brick business. This research is to measure how big the influence of BUMDES program implementation to economic empowerment of people in the Tonsewer Selatan Village, Tompaso Barat subdistrict, Minahasa district. By using method of quantitative research. Variabel in this study there are two that BUMDES program implementation (x) and economic empowerment of the community (y). Samples in this study totaling 75 consisting of 8 peoples manager BUMDES, 14 device village, 3 religious leaders, and 50 head of the family. Instruments in this study is likert scale and interview guides to get scores of BUMDES program implementation and economic empowerment of the community. Test used is a test the validity and reliability and technique is used technique simple linier regression analysis and analysis techniques product mement correlation.Keyword: Program Implementation, Economic Empowerment, Community